(untitled) (Journal of Medical & Health Sciences Review, 2025)
Aim: To explore the perceptions of key stakeholders regarding advanced practice nursing in Pakistan. Methodology: A qualitative case study research design was employed to facilitate an in-depth exploration of perceptions within a defined context. With a sample size of 11 determined by data saturation, purposive sampling was utilized as a data collection technique. Face-to-face, in-depth individual interviews were conducted, recorded, and analyzed. The study spanned six months, receiving approval from the ethical review boards of the Khyber Medical University. Results: Five themes emerged those were: Stakeholders’ views regarding advanced practice nursing, anticipated challenges and issues in introducing APN in Pakistan, Potential benefits of advanced practice nursing, Required Qualification and competencies for APN, Strategies for commencement of Advanced practice nursing Conclusion: The study explores the significance of advanced practice nursing in addressing the healthcare needs of Pakistan’s growing population. Recognizing it as a timely imperative, the findings highlight the need for nurses to elevate their knowledge and skills. Despite anticipated hurdles, the study concludes that advanced practice nursing holds the potential to enhance the overall healthcare system, emphasizing the importance of proactive measures to address challenges before initiation.